2017
DOI: 10.4049/jimmunol.1700757
|View full text |Cite
|
Sign up to set email alerts
|

CK12a, a CCL19-like Chemokine That Orchestrates both Nasal and Systemic Antiviral Immune Responses in Rainbow Trout

Abstract: Chemokines and chemokine receptors rapidly diversified in teleost fish but their immune functions remain unclear. We report here that Chemokine (C-C motif) ligand 19 (CCL19), a chemokine known to control lymphocyte migration and compartmentalization of lymphoid tissues in mammals, diversified in salmonids leading to the presence of six CCL19-like genes named CK10a, CK10b, CK12a, CK12b, CK13a and CK13b. Salmonid CCL19-like genes all contain the DCCL conserved motif but share low amino acid sequence identity. CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 99 publications
(131 reference statements)
0
21
0
Order By: Relevance
“…Histological changes in the OO were paralleled by changes in innate immune gene expression. Specifically, we observed a significant upregulation of ck10 , a CCL19-like chemokine in rainbow trout (Sepahi et al, 2017), and ptgs2b in OO 15 min after IHNV delivery. In the OB, in turn, we observed a significant downregulation in expression of ck10 and no significant change in expression of ptgs2b (Figure 4A).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Histological changes in the OO were paralleled by changes in innate immune gene expression. Specifically, we observed a significant upregulation of ck10 , a CCL19-like chemokine in rainbow trout (Sepahi et al, 2017), and ptgs2b in OO 15 min after IHNV delivery. In the OB, in turn, we observed a significant downregulation in expression of ck10 and no significant change in expression of ptgs2b (Figure 4A).…”
Section: Resultsmentioning
confidence: 76%
“…We previously reported that nasal delivery of live attenuated IHNV results in the recruitment of myeloid and lymphoid cells to the local nasal environment 4 days after treatment in trout (Sepahi et al, 2017; Tacchi et al, 2014). Here, we report that leukocyte recruitment occurs as early as 15 min after IHNV delivery as visualized by the enlarged lamina propria (LP) of the olfactory lamellae of IHNV-treated fish compared to control fish (Figure S4A-C).…”
Section: Resultsmentioning
confidence: 99%
“…* In humans and mice, ccl19 is implicated in lymphocyte migration and is important to define compartments within lymphoid tissues. In rainbow trout, one of the six ccl19 paralogues present in the genome participate to antiviral immunity though promotion of mucosal and central CD8+ T cell response (67).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IgM, IgT, IL-10, IL-1β, TGFβ-1a, TGFβ-1b and TNF-α was measured by RT-qPCR using specific primers (Table 2). qPCR was performed using 3μl cDNA template using specific primers as explained elsewhere (Sepahi, et al, 2017). Analysis was performed using the Pfaffl method (Pfaffl, 2001).…”
Section: Methodsmentioning
confidence: 99%